The history of metals in America - Simcoe, Charles R. (ASM International, 2018)
"The History of Metals in America chronicles the development of metals as both an industrial activity and a science. Progress involving structural metals made possible the air, land, sea, and space travel of today, skyscrapers reaching over 100 stories high, and many other engineering accomplishments that continue to shape modern society. This lively book takes the reader on a fascinating journey through the evolution of metals and metallurgy from the beginning of iron production in colonial times with the first iron plant in 1645 to the prevailing metals of the 21st century. Each chapter describes the development of a metal or series of metal alloys, industry growth, and modern uses in manufacturing. It includes chapters on cast iron, wrought iron, alloy steels, tool steels, stainless steels, nickel-base superalloys, aluminum, and titanium. Other chapters cover the science of metals as it developed from 1890 to 1950 and the biographies of the pioneers of metals research. The final chapters cover the formation, growth, and decline of the integrated steel industry and the rise of a new industry in steel minimills. The History of Metals in America will appeal to readers in all sectors of the materials industry, students and faculty of engineering programs, middle and high school American history students, and anyone interested in the history of technology, travel, tools, and machinery in the U.S."--